2005
DOI: 10.2460/ajvr.2005.66.77
|View full text |Cite
|
Sign up to set email alerts
|

Duration of effect and effect of multiple doses of topical ophthalmic 0.5% proparacaine hydrochloride in clinically normal dogs

Abstract: Duration of corneal anesthetic effect induced by topical ophthalmic application of 0.5% proparacaine in dogs of this study is considerably longer than that reported elsewhere. Serial application of doses of 0.5% proparacaine increases the duration and magnitude of corneal anesthetic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
4
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 17 publications
7
57
4
3
Order By: Relevance
“…Moreover, this information is similar to those reported by Blocker and Van Der Woerdt (2001) in cats and by Brooks et al (2000) in horses. Barret et al (1991) and Herring et al (2005) observed that dolichocephalic dogs exhibit esthesiometry values of 1.75cm, similar to the results obtained in this study (1.7cm). Klaumann (2007) reported values varying from 1.5 to 2.5cm.…”
Section: Arqsupporting
confidence: 82%
See 4 more Smart Citations
“…Moreover, this information is similar to those reported by Blocker and Van Der Woerdt (2001) in cats and by Brooks et al (2000) in horses. Barret et al (1991) and Herring et al (2005) observed that dolichocephalic dogs exhibit esthesiometry values of 1.75cm, similar to the results obtained in this study (1.7cm). Klaumann (2007) reported values varying from 1.5 to 2.5cm.…”
Section: Arqsupporting
confidence: 82%
“…Despite Herring et al (2005) reporting that the proxymetacaine is the drug of choice for ocular surface anesthesia due to its minimal side effects, the manufacturer warns about possible ocular alterations following its administration, such as irritation, conjunctival hyperemia, tearing and corneal erosion.…”
Section: Arqmentioning
confidence: 99%
See 3 more Smart Citations